Maternal health literacy and pregnancy outcomes in Afghanistan - Mehran Rostamzadeh; Zainab Ezadi; Maryam Hosseini; Abbas Ali Husseini (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: A healthy pregnancy and its outcomes are highly dependent on maternal health literacy. This is the first study that targets the association between maternal health literacy and pregnancy outcomes of women in Afghanistan. MATERIALS AND METHODS: This is a cross-sectional study on 200 women who received a prenatal care program and have given birth at Barchi National - 100 beds hospital in Kabul, the capital city of Afghanistan. As a convenient sample, they answered Maternal Health Literacy and Pregnancy Outcome Questionnaire with 5-point Likert scales. We tested the correlation between maternal health literacy and pregnancy outcome scores via the Pearson's correlation coefficient. The potential association of socio-demographic and fertility variables with both maternal health literacy and pregnancy outcome was tested via independent samples t-test or one-way ANOVA. All analysis was performed with a 95% confidence level and a significant level was defined as a P value ≤0.05. RESULTS: The maternal health literacy of Afghan women is inadequate. Maternal health literacy is linked to pregnancy outcome, and both were associated with education level, age, number of gravidities, number of received care, and time that onset the prenatal care. Nutshell, we found evidence of a positive and significant correlation between maternal health literacy and pregnancy outcome. CONCLUSION: This study brings forth the novel data on maternal health literacy of Afghan women, the members of society that face health crises for more than half a century. This study calls for recognition that inadequate maternal health literacy in Afghanistan significantly influences prenatal care quality and perpetuates the biggest challenge for maternal and child health through pregnancy outcomes.